Fatal Pediatric Melioidosis and the Role of Hyperferritinemic Sepsis-Induced Multiple-Organ Dysfunction Syndrome - Anand, Mohan; Malini, Paranchothy; Sakthy, Segaran; Richard Siu, Chiu Wong; Yek Kee, Chor; Yuwana, Podin; Mong How, Ooi (2 The American Society of Tropical Medicine and Hygiene, 2022)
Melioidosis is reported to cause a high fatality rate in children, even in the absence of risk factors for disease. The aim of this study was to identify characteristics of fatal pediatric melioidosis infection. We performed a retrospective analysis of children aged , 15 years with culture-confirmed melioidosis admitted to Bintulu Hospital in Sarawak, Malaysian Borneo, from January 2011 to December 2020. Forty-one children had culture-confirmed melioidosis. Nine (22%) had a fatal outcome; 8 (89%) had no predisposing risk factors. Bacteremia, septic shock, and acute respiratory distress syndrome were present in all fatalities. Demographic characteristics, presenting manifestation, and disseminated infection were not significantly associated with mortality, whereas the presence of splenomegaly, cytopenia, disseminated intravascular coagulation, and hepatobiliary dysfunction, all of which are features of hyperferritinemic sepsisinduced multiple-organ dysfunction syndrome, were associated with mortality. Hyperferritinemic sepsis-induced multiple-organ dysfunction syndrome may be a key component in the pathogenesis of fatal pediatric melioidosis.